EDUCATION AND REGIONAL ECONOMIC GROWTH IN CENTRAL JAVA - Jamzani Sodik; Didi Nuryadin (Economic Journal of Emerging Markets)
There has been a long debate on the relationship betwen investment on human resources and economic growth. This paper examines the affect of investment and three level of education, namely elementary school, junior high school, and senior high school, on regional economic growth in Central Java. It estimates a General Least Square on a pool data of 35 districts from 2004 to 2008. The results suggest that regional economic growth is influenced by investments and the growth of junior high school attainment. However the growth of senior high school attainment and growth of elementary school attainment do not affect regional economic growth.